PERCEIVED INFLUENCE OF SOCIAL NETWORKSITE USAGE ON THE LEARNING HABITS OF STUDENTS’ IN TERTIARY INSTITUTIONS IN NIGERIA - Egba, A. Fraser (BW Academic Journal, 2022)
The study investigates the perceived influence of social networking on the learning habit of students in Nigeria. The study specifically examined students’ activities online, the effect of SN usage on their study habit and its influence on students’ socialization habit. To achieve results, four research questions were formulated and the descriptive survey design was adopted for this study. Five (5) tertiary institutions were randomly selected in Rivers state while the stratified random sampling technique was used to select Two Hundred and Fifty (250) respondents from the schools. A thirty two (32) item questionnaire was developed and validated by experts in the department of measurement and evaluation in Federal College of Education (Technical), Omoku, Rivers state. The reliability of the instrument stood at 0.86 and data collected was analyzed using the mean (). The findings of the study show that most of the students invest large amount of their quality time on social networking, and the influence of social networking on study habit and socialization habit of students is more negative than positive.